Perspectives and perceptions in developing a moral education programme - Beddoe, Innocent B. (School of Education, The University of the West Indies, 1983)
This paper (a) presents some major perspective and theoretical formulations in moral education, (b) suggests a comprehensive approach to moral education, and (c) describes the development process in FRONTLINE, a national moral education programme in Trinidad and Tobago.
Keywords: Moral education